2011
DOI: 10.1093/brain/awr041
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal chloride accumulation and excitatory GABA underlie aggravation of neonatal epileptiform activities by phenobarbital

Abstract: Phenobarbital produces its anti-epileptic actions by increasing the inhibitory drive of γ-aminobutyric acid. However, following recurrent seizures, γ-aminobutyric acid excites neurons because of a persistent increase of chloride raising the important issue of whether phenobarbital could aggravate persistent seizures. Here we compared the actions of phenobarbital on initial and established ictal-like events in an in vitro model of mirror focus. Using the in vitro three-compartment chamber preparation with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
176
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(181 citation statements)
references
References 87 publications
4
176
1
Order By: Relevance
“…3). In agreement with previous studies of chloride homeostasis, we found that the recovery of depolarizing GABA A R responses could be estimated using an exponential fit (Brumback and Staley, 2008;Nardou et al, 2011). Under control conditions we found that the recovery rate had a time constant of 34.7 Ϯ 2.8 s and that this was not affected by AR blockade with CGS 15943, when the mean time constant was 31.6 Ϯ 3.0 (p ϭ 0.22, n ϭ 8, paired t test).Together, these results show that changes in Cl Ϫ homeostasis mechanisms are unlikely to contribute to the attenuation of the GABA A R-mediated potentials.…”
Section: Endogenous Adenosine Release Modulates Seizure Duration and supporting
confidence: 90%
“…3). In agreement with previous studies of chloride homeostasis, we found that the recovery of depolarizing GABA A R responses could be estimated using an exponential fit (Brumback and Staley, 2008;Nardou et al, 2011). Under control conditions we found that the recovery rate had a time constant of 34.7 Ϯ 2.8 s and that this was not affected by AR blockade with CGS 15943, when the mean time constant was 31.6 Ϯ 3.0 (p ϭ 0.22, n ϭ 8, paired t test).Together, these results show that changes in Cl Ϫ homeostasis mechanisms are unlikely to contribute to the attenuation of the GABA A R-mediated potentials.…”
Section: Endogenous Adenosine Release Modulates Seizure Duration and supporting
confidence: 90%
“…6 The present article provides the first case example in which a behavioral disinhibition to a benzodiazepine was noted and used as a rationale to initiate bumetanide treatment. Indeed, adverse effects to GABA-enforcing agents have been experimentally linked to disturbed chloride homeostasis, 18,19 and behavioral disinhibition after benzodiazepine treatment is a common phenomenon 2,3,20-24 also noted in patients with ASD. 4 Bumetanide led to a remarkable improvement in sensory behaviors, rigidity, memory, and learning in our patient, which suggested that the diuretic had improved neural functioning.…”
Section: Discussionmentioning
confidence: 99%
“…NKCC1 is the principal transport mechanism responsible for Cl − uptake and for the depolarizing GABA A R responses of immature neurons 10,94,97 (TABLE 1). By contrast, in some other neuronal populations, such as the brainstem superior olivary complex, other — probably HCO 3 − -dependent — mechanisms of Cl − uptake are important 69 .…”
Section: Expression Of Cccs In the Cnsmentioning
confidence: 99%